Synthesis of γ-Fe2O3, Fe3O4 and copper doped Fe3O4 nanoparticles by sonochemical method - Kannusamy Mohanraj,; Ganesan Sivakumar, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Nanoparticles of undoped and copper doped with Fe3O4 of three concentrations (0.5, 1.0 and 1.5) are synthesized by sonochemical method. Structural, optical and morphological properties of these compounds were studied. Fe2+/Fe3+ ratio is found to be 2.36. Crystalline structure, lattice parameters, surface morphologies, direct and indirect band gap energies of the synthesized compounds were estimated and the results are discussed in detail. The XDR analysis indicates the Cu doped Fe3O4 nanoparticles have higher crystallinity than undoped samples. Average crystallite size is found to increase as Cu concentration increased. The FTIR results are proven by the presence of mixed magnetite-hematite nanostructures and it is complement to the XRD results. The presence of spherical, polygonal and agglomeration forms of the particles are visually seen in the SEM images. Direct and indirect band gap energy is found to be decreased as the copper concentration was increased.